Interaction between paraventricular nucleus and septal area in the control of physiological responses induced by angiotensin II - Camargo, L.A.A. [UNESP]; Saad, W.A. [UNESP]; Simões, S.; Santos, T.A.B.; Saad, W. Abrão (Associação Brasileira de Divulgação Científica (ABRADIC), 2002)
We determined the effects of losartan (40 nmol) and PD 123319 (40 nmol) (both non-peptides and selective antagonists of the AT1 and AT2 angiotensin receptors, respectively), and [Sar¹, Ala8] angiotensin II (ANG II) (40 nmol) (a non-selective peptide antagonist of angiotensin receptors) injected into the paraventricular nucleus (PVN) on the water and salt appetite, diuresis and natriuresis and mean arterial pressure (MAP) induced by administration of 10 nmol of ANG II into the medial septal area (MSA) of male Holtzman rats weighing 250-300 g. The volume of drug solution injected was 0.5 µl over a period of 10-15 s. The responses were measured over a period of 120 min. ANG II alone injected into the MSA induced an increase in all the above parameters (8.1 ± 1.2, 1.8 ± 0.3, and 17.1 ± 1.0 ml, 217 ± 25 µEq/120 min, and 24 ± 4 mmHg, respectively, N = 10-12) compared with vehicle-treated rats (1.4 ± 0.2, 0.6 ± 0.1, and 9.3 ± 0.5 ml, 47 ± 5 µEq/120 min, and 4.1 ± 0.8 mmHg, respectively, N = 10-14). Pretreatment with losartan and [Sar¹, Ala8] ANG II completely abolished the water and sodium intake, and the pressor increase (0.5 ± 0.2, 1.1 ± 0.2, 0.5 ± 0.2, and 0.8 ± 0.2 ml, and 1.2 ± 3.9, 31 ± 4.6 mmHg, respectively, N = 9-12), whereas losartan blunted the urinary and sodium excretion induced by ANG II (13.9 ± 1.0 ml and 187 ± 10 µEq/120 min, respectively, N = 9). Pretreatment with PD 123319 and [Sar¹, Ala8] ANG II blocked the urinary and sodium excretion (10.7 ± 0.8, 9.8 ± 0.7 ml, and 67 ± 13 and 57 ± 17 µEq/120 min, respectively, N = 9), whereas pretreatment with PD 123319 partially blocked the water and sodium intake, and the MAP induced by ANG II administration (2.3 ± 0.3, 1.1 ± 0.1 ml, and 12 ± 3 mmHg, respectively, N = 9-10). These results suggest the angiotensinergic effect of the MSA on the AT1 and AT2 receptors of the PVN in terms of water and sodium homeostasis and MAP modulation.
Keywords: AT1 receptors; AT2 receptors; Water; Sodium; Paraventricular nucleus; Medial septal area